Interactive Media Innovation in Social Studies Learning to Support Pancasila Student Profile in Elementary Schools - Irmayani Halim; Winda Anggriyani Uno (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aimed to analyze the implementation of interactive media in social studies learning to support the development of the Pancasila Student Profile in elementary schools. Previous studies have highlighted the lack of student engagement in traditional social studies learning, yet few have explored the integration of interactive media specifically targeted at the Pancasila Student Profile dimensions. To fill this gap, this research utilized a qualitative descriptive approach conducted at an elementary school involving 25 fourth-grade students. Data were collected systematically through classroom observation, semi-structured interviews with teachers and students, and learning documentation. The results showed that the use of interactive media—such as animated learning videos, digital quizzes, and interactive educational applications—significantly improved students' engagement and conceptual understanding. Active student participation increased from 36% to 72%, and learning mastery improved from 40% to 68%. Furthermore, the implementation strongly supported key dimensions of the Pancasila Student Profile, specifically critical thinking, creativity, collaboration, and global diversity awareness. The study concludes that integrating interactive media in social studies learning effectively enhances learning quality, transforms passive learning environments into active ones, and successfully supports holistic curriculum goals in elementary education.